2018
DOI: 10.1108/jeim-11-2016-0187
|View full text |Cite
|
Sign up to set email alerts
|

ECM implementations in practice: objectives, processes, and technologies

Abstract: Purpose Enterprise content management (ECM) is an important topic in information management, but researchers have long had difficulty developing a consistent definition. The purpose of this paper is to analyze ECM case reports from practice to identify ECM’s objectives, processes and technologies and to provide a foundation on which ECM can be conceptualized and defined. Design/methodology/approach This paper assembles more than 1,200 case reports on industrial ECM implementations in order to characterize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Statistical analysis reveals that creators’ number of followers and total likes were associated with video performance in terms of user engagement, suggesting that, similar to other social media platforms, accounts with a greater follower base on TikTok receive higher engagement with content, since creators can amplify their content to larger audiences. This finding aligns with previous research on the association between creator characteristics and user engagement on social media, including Instagram 53 and Twitter, 54 which concluded that creator-related factors, particularly the number of followers, play a significant role among factors associated with user engagement and virality. However, findings from our study indicate that there was no significant difference between creator characteristics and user engagement among pro–eating disorder, anti–eating disorder, and prorecovery content, which may be attributed to the recent modifications to TikTok’s algorithm 55 to recognize and break up patterns of content with the same negative themes to minimize the recommendation of limited types of content that may have a negative influence on users when viewed in a filter bubble, such as extreme dieting.…”
Section: Discussionsupporting
confidence: 91%
“…Statistical analysis reveals that creators’ number of followers and total likes were associated with video performance in terms of user engagement, suggesting that, similar to other social media platforms, accounts with a greater follower base on TikTok receive higher engagement with content, since creators can amplify their content to larger audiences. This finding aligns with previous research on the association between creator characteristics and user engagement on social media, including Instagram 53 and Twitter, 54 which concluded that creator-related factors, particularly the number of followers, play a significant role among factors associated with user engagement and virality. However, findings from our study indicate that there was no significant difference between creator characteristics and user engagement among pro–eating disorder, anti–eating disorder, and prorecovery content, which may be attributed to the recent modifications to TikTok’s algorithm 55 to recognize and break up patterns of content with the same negative themes to minimize the recommendation of limited types of content that may have a negative influence on users when viewed in a filter bubble, such as extreme dieting.…”
Section: Discussionsupporting
confidence: 91%
“…The success of Internet banking is based on continuous use instead of initial adoption (Yuan et al , 2019). The term continuance is defined as the extent wherein technology users intend to continue use of Internet banking services and focus on post-consumption experiences (Jaakonmäki et al , 2018; Rahi et al , 2020; Yuan et al , 2019). Contrary to this, adoption is a degree where a user takes decision to use a particular service at initial stages and intend to use these services (Bhattacherjee, 2001; Lee and Kim, 2020a).…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular matrix (ECM) is composed of glycoproteins, elastin, collagen, and hyaluronic for providing solid structural support for cellular processes, i.e., proliferation, cell migration, and growth [94]. Moreover, ECM also systematizes the intracellular communication of cytokines and growth factors and acts as a source of physical barrier against the tumor microenvironment [95]. However, in solid metastatic tumors, the ECM equilibrium in maintaining homeostasis gets affected, leading to disorganization of the physicochemical and biochemical features, as shown in Figure 3.…”
Section: Rna-nanomaterials For Targeted Therapy Of Different Cancersmentioning
confidence: 99%